Larval morphology and ontogeny of Nasikabatrachus sahyadrensis Biju & Bossuyt, 2003 (Anura, Nasikabatrachidae) from Western Ghats, India - Raj, Prudhvi; Vasudevan, Karthikeyan; V., Deepak; Sharma, Richa; Singh, Shashi; Aggarwal, Ramesh K.; Dutta, Sushil K. (Zootaxa, 2012)
The external, oral and buccopharyngeal morphologies of Nasikabatrachus sahyadrensis tadpoles were studied using ste-reoscopic and scanning electron microscopy. Using DNA barcodes, taxonomic identity of the tadpoles was establishedand tadoples of N. sahyadrensis were reared in semi-natural conditions. Development in the species from hatching tometamorph was prolonged and it took about 100 days for the freshly hatched larvae to metamorphose. The tadpoles areexotrophic, torrent dwelling with a large ventral suctorial oral disc, broadly rounded snout, cylindrical body, and a funnelshaped vent tube opening medially. During development external and buccopharyngeal characters show extensive changes. During metamorphosis developmental asynchrony was observed.